2015
DOI: 10.1039/c5ta02276b
|View full text |Cite
|
Sign up to set email alerts
|

Sodium borohydride hydrazinates: synthesis, crystal structures, and thermal decomposition behavior

Abstract: . (2015). Sodium borohydride hydrazinates: synthesis, crystal structures, and thermal decomposition behavior. Journal of Materials Chemistry A, 3 (21), 11269-11276. Sodium borohydride hydrazinates: synthesis, crystal structures, and thermal decomposition behavior AbstractMetallic borohydride hydrazinates are novel boron-and nitrogen-based materials that appear to be promising candidates for chemical hydrogen storage. Herein, sodium borohydride hydrazinates, including NaBH 4 ·N2H 4 and NaBH 4 ·2N 2 H 4 , were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…This could be due to the formation of excessive borohydride–amine complexes upon the reaction of NH 2 with BH 4 − at a higher concentration of amine. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the formation of excessive borohydride–amine complexes upon the reaction of NH 2 with BH 4 − at a higher concentration of amine. [ 25 ]…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the formation of excessive borohydride-amine complexes upon the reaction of ─NH 2 with BH 4 À at a higher concentration of amine. [25] For the TDA-stabilized NaBH 4 , the undefined morphologies of NaBH 4 -TDA-2.5 evolved into bar-like morphologies of increasing length for TDA concentration above 5 mM (Figure 2d and Figure S6, Supporting Information). Only spherical NaBH 4 nanoparticles were previously observed at a TDA concentration as low as 100 μM, [11b] and this indicates that TDA has two critical micelle concentrations (CMCs), which direct the growth of NaBH 4 into the sphere and/or bar-like nanostructures.…”
Section: Synthesis Of Varied Nabh 4 Morphologiesmentioning
confidence: 99%
“…3C, S1A). Moreover, typical peaks of AgNPs, prepared by chemical reduction, at ≈1500 cm -1 and 1650 cm -1 also appear [34]. X-ray photoelectron spectroscopy (XPS) demonstrates the appearance of 3.1 % of Zr after in situ growth of UiO-66 (Tab.…”
Section: Characterization Of Pet@uio-66-ag25mentioning
confidence: 99%
“…5,6 In the past few decades, great attention has been paid to both hydrogen production technologies and a variety of hydrogen storage methods, [7][8][9][10] including the use of different compounds, 11,12 especially complex hydrides, of which borohydrides are typical representative. [13][14][15] These solid-state hydrogen storage materials offer some advantages over high pressure gaseous storage and low temperature liquid storage, such as high capacity, high safety, and low cost. In particular, alkali metal borohydrides are regarded as possible hydrogen carries, ascribed to their contribute to their high gravimetric and volumetric hydrogen density, together with good stability.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of improving the thermodynamic and kinetic properties of the thermal decomposition of NaBH 4 , many strategies have been taken, such as adding catalyst, building thermodynamic destabilization system, nano-engineering and chemical modications. 13,[23][24][25] For instance, NaBH 4 /MgH 2 system could full its decomposition before melting due to the formation of MgB 2 in the system. 26 Czujiko et al suggested that pure Mg could lower down the desorption temperature of NaBH 4 through catalytic effect.…”
Section: Introductionmentioning
confidence: 99%